Gender-Sensitive Safety System sebagai Strategi Pemasaran dan Retensi Mitra Perempuan pada Transportasi Online - Huriyah, Sari; Yulihasri; Fahmi, Rahmi (SAFE-Network, 2025)
This study aims to evaluate the implementation of safety and protection systems against sexual harassment experienced by female online transportation partners, particularly Gojek drivers, in Padang City. The phenomenon indicates that although these partners are not permanent employees, they face similar, or even greater, occupational risks, especially for women. Using a qualitative approach with a phenomenological method, the research explores the in-depth experiences of seven informants who have encountered sexual harassment. Data were collected through in-depth interviews and analyzed using the Grand Theory of Behavior-Based Safety and the Normalization Process Theory. The findings reveal that sexual harassment, both verbal and non-verbal, remains prevalent and has a significant impact on mental health, sense of security, and psychological well-being. Many victims choose not to report incidents due to low trust in reporting systems, lack of follow-up, and fear of losing income. The study finds that the existing safety and protection systems are not yet optimal, particularly in prevention, training, and case handling. This research contributes to the literature on occupational safety management and the protection of female workers in the digital economy sector, while also providing policy recommendations that are more responsive, inclusive, and victim-centered.